Interrelations of Ethics and Management in Business - Khoshbakht, Farnoosh (ՀԱԱՀ հիմնադրամ)
Nowadays, the only key to survive in the competitive market is to understand all marketing rules and aspects. The most crucial concepts in this field are related to managerial, ethical and economic issues and the interrelations of these three indicators. Ethical issues are not only directly connected with businesses, but also compose corporations’ activities in accordance with global marketing regulations. By means of ethical issues managers can make SWOT analysis to overcome the problems inside and beyond the corporations. In this study the author attempts to show the correlation of these three indicators by regression and Spearman’s analysis as statistical approaches.
Keywords: Agricultural Economics and Agribusiness